2012
DOI: 10.3390/polym4010880
|View full text |Cite
|
Sign up to set email alerts
|

Spiral Assembly of the 1D Chain Sheet of Fe(NCBH3)2(bpa)2·(biphenyl) (bpa = 1,2-bis(4-pyridyl)ethane) and its Stepwise Spin-Crossover Phenomenon

Abstract: Abstract:The assembled complex, Fe(NCBH 3 ) 2 (bpa) 2 , enclathrating biphenyl has been synthesized, the skeleton of which is a 1D chain. Several 1D chains gather together to form 1D chain sheet. The 1D chain sheet is stacked spirally to form novel spiral assembly. The average Fe-N distances were 2.020(2), 2.083(2), and 2.191(2) Å at 100, 175, and 298 K, respectively, reflecting spin-state change of the iron ion. The assembly showed a stepwise spin-crossover phenomenon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…From the point of view of space-filling, 1D chain and biphenyl molecule formed a crystal, leading to the threefold spiral structure. Such structure conducts stepwise SCO if the anionic ligand is changed from NCS − to NCBH 3 − , as reported by the present author et al [25]. Although the propeller structure of pyridines around the iron atom is a key point to showing SCO, the slight difference in ligand field between NCS − to NCBH 3 − also affects the SCO phenomenon.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…From the point of view of space-filling, 1D chain and biphenyl molecule formed a crystal, leading to the threefold spiral structure. Such structure conducts stepwise SCO if the anionic ligand is changed from NCS − to NCBH 3 − , as reported by the present author et al [25]. Although the propeller structure of pyridines around the iron atom is a key point to showing SCO, the slight difference in ligand field between NCS − to NCBH 3 − also affects the SCO phenomenon.…”
Section: Discussionsupporting
confidence: 83%
“…This shows that the ligands can easily approach iron in the chiral propeller type local structure when the spin state becomes an LS state. It had been reported that [Fe(NCS)2(bpa)2]n has a 1D chain structure and shows HS state [25]. We became interested in [Fe(NCS)2(bpa)2]n, because the bpa has an anti-gauche conformation and NCS − can be changed with other anionic ligands.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The BH 3 CN – anion is also suitable for designing polymeric SCO complexes. They can be 1D helical chains, 2D square grid networks, or even 3D porous coordination polymers when a tetradentate N,N′-bridging ligand is used. In the case when large aromatic ligands are employed, pores of various sizes can be achieved.…”
Section: Introductionmentioning
confidence: 99%